Implementing Healthy Lifestyles Through Nutritious Eating Habits in Early Childhood: A Case Study at Mutiara Kindergarten, West Aceh - Hasanah, Janatul; Kustina, Rika; Fidiawati, Liza (CV. Dyoqu Publishing Management, 2025)
Background: Early childhood is a golden period that greatly determines growth and development in later life. However, parents' busy work schedules often result in suboptimal provision of nutritious food for children, who are more often given low-nutrient ready-to-eat meals. This condition has an impact on the low level of healthy lifestyle habits from an early age. Aims: This study aims to describe the implementation of healthy lifestyles through the habit of eating nutritious food in children aged 4–5 years and to identify the obstacles encountered in its implementation at Mutiara Bangsa Kindergarten, Kaway XVI District, West Aceh Regency. Methods: This study used a qualitative field research approach. Data were collected through observation, structured interviews with five parents and several teachers, and documentation. The research instruments consisted of observation sheets, child development assessment rubrics, and interview guides. Data analysis was conducted using the Miles and Huberman interactive model, which included data reduction, data presentation, and conclusion drawing, and was tested for validity through source triangulation. Results: The results showed that most children had begun to adopt clean and healthy habits and brought nutritious meals from home. Teachers actively guided children in group meals, limited snacks from outside, and instilled an understanding of healthy food. The main obstacles faced were parents' limited time to prepare healthy meals, children's tendency to choose food based on taste, and the influence of unhealthy snacks around the school. Conclusion: The implementation of a healthy lifestyle through nutritious eating habits has proven to be effective in fostering healthy habits in early childhood, while also supporting children's physical and cognitive development. Continuous collaboration between teachers and parents is needed to maintain the consistency of the program, as well as the expansion of its implementation in other early childhood education institutions in an effort to shape a generation of children who are healthy, intelligent, and resilient from an early age.